Analysis of energy consumption for neutralization of the wastewater treatment plants sludge - Ion Nicolae; Mihăescu Lucian; Ionescu Gabriela; Pop Elena; Negreanu Gabriel Paul; Safta Carmen Anca (E3S Web of Conferences)
Starting from the concept of a circular economy applied to wastewater treatment plants, the present work aims to find a method to neutralize the sludge from the wastewater treatment technological cycle. It is thus proposed to dry the sludge in a rotary drum installation. The fuel used is natural gas and its consumption required for sludge drying is determined. The fuel consumption analysis is determined for different quantities of sludge that resulted in the technological process of wastewater treatment. The waste sludge has different moisture contents. Also, the analysis is done with and without the presence of volatiles in the waste sludge composition.